ONLINE FEEDBACK IMPACT ONLINE SHOPPERS' IMPULSE PURCHASES IN MALAYSIA - Lu Man Hong; Wan Farha Wan Zulkiffli; Che Adawiah Che Amran (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2021)
Online shopping has risen to the third position among Malaysians who use the Internet. Typically, past customer online reviews are deciding factors for an online business's success or failure because online consumers encounter online reviews while visiting a website, and it has a direct effect on their ability to purchase impulsively and online impulse buying conduct. The majority of previous research on market-generated context as a factor in online impulse buying behaviour has concentrated on the market-generated background. As a result, this research identified two types of online reviews as independent variables: hedonic and utilitarian value online reviews, browsing, and willingness to buy impulsively as mediating and moderating variables. While online impulse buying behaviour a dependent variable. This study only involves online shoppers who have made at least one purchase on both Lazada Malaysia and Shopee Malaysia websites. This study took a quantitative approach, with 100 responses collected from online shoppers who had made at least one purchase on Shopee Malaysia and Lazada Malaysia through an online questionnaire. Due to the deletion of one straight-lining response, 99 responses were subjected to data analysis using SmartPLS software. According to the results, hedonic value online reviews influence browsing, and browsing influences the urge to buy impulsively and directly to online impulse purchasing.